Organizational Commitment Among Civil Servant: The Role of Work Meaningfulness - Elvita Bellani; Sri Wahyuni; Amelia Rizkawani Azwar (Universitas Negeri Makassar, 2022)
Organizational commitment and work meaningfulness are very important for employees to have, but research related to this is still limited, especially on civil servants. This research aims to investigate the relationship between work meaningfulness and organizational commitment of civil servants of East Kalimantan Province. A total of 72 civil servants participated in this study. Data is collected using a scale Organizational Commitment Questionnaire dan Work and Meaning Inventory. The result revealed that work meaningfulness significantly contributes to organizational commitment with an R2 value of 0.708, p <0.01.